Association Between Trypanosoma cruzi DNA in Peripheral Blood and Chronic Chagasic Cardiomyopathy: A Systematic Review - Bosch-Nicolau, Pau; Espinosa-Pereiro, Juan; Salvador, Fernando; Sánchez-Montalvá, Adrián; Molina, Israel (Frontiers in Cardiovascular Medicine, 2022)
Chronic chagasic cardiomyopathy (CCC) is the most important complication of patients with Chagas disease (CD). The role of persistent detection of DNA in peripheral blood and its association to CCC is unknown. We performed a systematic review up to July 2021, including studies that reported ratios of CCC and PCR positivity among non-treated adult patients. We identified 749 records and selected 12 for inclusion corresponding to 1,686 patients. Eight studies were performed in endemic countries and 4 in non-endemic countries. Only two studies showed an association between CCC and Trypanosoma cruzi parasitemia by means of PCR detection. Six studies reported greater positive PCR ratios among patients with CCC than in the patients with indeterminate chagas disease (ICD) with no statistical significance. A significant risk of bias has been detected among most of the studies. Therefore, while we performed a meta-analysis, wide inter-study heterogeneity impeded its interpretation. Conclusions With the available information, we could not establish a correlation between PCR-detectable parasitemia and CCC. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020216072, identifier: CRD42020216072.